A calibration-verification testbed for electrical energy meters under low power quality conditions. (December 2021) - Callegaro, Luca; Aprile, Giulia; Cultrera, Alessandro; Galliana, Flavio; Germito, Gabriele; Serazio, Danilo; Trinchera, Bruno
Abstract: A calibration/verification testbed for electrical energy meters is under development at the Istituto Nazionale di Ricerca Metrologica, the National Metrology Institute of Italy. The testbed will be employed for the calibration of commercial static power energy meters under low power conditions and for simulating the verification in the field of energy meters under real operational conditions. The activity is in collaboration with the Ministry for Economic Development and aims to the future development of regulatory documents for energy metering verification.